1992
DOI: 10.1111/j.1365-2648.1992.tb01849.x
|View full text |Cite
|
Sign up to set email alerts
|

A view of the phenomenon of caring in nursing practice

Abstract: Care is regularly used as a suffix to nursing, in such well-known phrases as 'total nursing care' and 'holistic nursing care'. While most care is provided by lay persons, there is little nursing research which focuses on the meaning of care, particularly in relation to the United Kingdom. This small-scale study investigates the meaning of care from the experience of six practising staff nurses in a British hospital and leads to a view of this phenomenon. Phenomenology was the chosen methodology, which facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 18 publications
7
88
0
Order By: Relevance
“…Parish (1986) portrayed quality nursing as involving emotional support and comfort; whilst Smith (1991), Savage (1995), Phillips (1996) and Staden (1998) identified the importance of the ‘emotional labour of nursing’. Nurses in Clark and Wheeler’s (1992) study perceived that caring related more to interpersonal aspects of care rather than with the tasks a nurse performs; more recently Idvall and Rooke (1998) found that promoting relationships and giving emotional and social support are important aspects of quality care. Thorne (1988) reported that patients perceived that communication with health care professionals was important in enhancing care quality; patients described ‘helpful communications’ as being constructive, encouraging and supportive, whilst ‘unhelpful communications’ were frustrating, impeding and demoralizing.…”
Section: Discussionmentioning
confidence: 99%
“…Parish (1986) portrayed quality nursing as involving emotional support and comfort; whilst Smith (1991), Savage (1995), Phillips (1996) and Staden (1998) identified the importance of the ‘emotional labour of nursing’. Nurses in Clark and Wheeler’s (1992) study perceived that caring related more to interpersonal aspects of care rather than with the tasks a nurse performs; more recently Idvall and Rooke (1998) found that promoting relationships and giving emotional and social support are important aspects of quality care. Thorne (1988) reported that patients perceived that communication with health care professionals was important in enhancing care quality; patients described ‘helpful communications’ as being constructive, encouraging and supportive, whilst ‘unhelpful communications’ were frustrating, impeding and demoralizing.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the lived and spoken meanings of the carers themselves liberates the meanings and expenences of the phenomenon called care (Clarke & Wheeler 1992) The ahove quotation relates to professional (nursing) carers, but pomts the way to a better imderstanding of all canng circvunstances However, before a more holistic picture of the dimensions of care can be achieved, we would suggest that there should be a change m emphasis away from 'nursmg care' towards 'family care' McFarlane (1976) highlighted the need to take full accoimt of the family and patients' perspective on care and not just focus on the professionals' views Yet, with a few exceptions (Kitson 1987), this issue has rarely heen addressed More recently, the need to consider the impact of nursmg care on patient outcomes has been stressed (Morse et al 1990), but the meanmg of care from a family carer's viewpoint has either been ignored or taken as read This situation is unacceptable…”
Section: Common Featuresmentioning
confidence: 99%
“…In addition to the above, other typologies of nursmg care underpins nursmg activity (McFarlane 1976, Kitson 1987, have been developed (Swanson 1991, Clarke & Wheeler Morse et al 1990, Clarke & Wheeler 1992 Indeed, it has 1992), but despite these efforts it is still considered that an acceptable definition has yet to be reached ( IS argued that attempts to achieve a more precise defimtion A typoloQT of family care of care, thereby reducmg the concept to actions or structures, are 'philosophically naive' and disr^ard canog's uniquely mdividual nature, thereby stnppmg it of its contextual elements (Phillips 1993) However because no two canng contexts are identical, actions which constitute canng can only be identified by skilled assessment of the situation, and not by some universally applicable theory or rule (Phillips 1993) …”
Section: Introductionmentioning
confidence: 98%
“…This interest is represented by an expanding nursing literature on the topic and a growing debate which examines this concept from a variety of perspectives (e.g. Benner & Wrubel 1989, Forrest 1989, Swanson 1991, Clarke & Wheeler 1992, Barker et al . 1995, Bottoroff et al .…”
Section: The Nature Of Caring Theorymentioning
confidence: 99%